El sistema de personajes de la novela Mandíbula de Mónica Ojeda - Siguencia Pacheco, Sofía Marina (2024)
This thesis analyzes the character features in Mandíbula Novel by Ecuadorian writer Mónica Ojeda. The researcher performed the analysis using the Greimas semiotic model. The novel tells the story of a teenage girl kidnapped by her teacher. The story explores themes such as violence and complex relationships between women. This study used a descriptive/bibliographic qualitative approach. In addition, this work used techniques such as documentary analysis and analytical reading. It is based on the educational sciences because it studies the educational area using a humanistic approach. Greimas' semiotic theory is applied to analyze narrative programs, identify actors, obtain lexematic figures, and describe the roles of the characters. Greima's theory allows a deep understanding of the novel functionality and characteristics. The researcher performed an analysis of each one of the chapters in sequence because of the chapter sequences and the temporal jumps in the story. The study identified eight character roles that changed throughout the story. In general, Clara played the central role in the narrative. The lexematic figure identified was the trauma of being a teacher. The analysis of the table of competencies determined that Clara fulfilled the central role. The research concluded that the character system was constructed with acting roles that interchanged according to the narrative perspective. Trauma determines the personality of the antagonist. The semiotic analysis of this contemporary work seeks to value Ecuadorian literature and contribute to its critical study. The application of Greimas allowed a deep understanding of the characters and their functionality in the plot of the novel Mandíbula.